Synthesis and crystal structure of some first row transition metals containing a common Schiff base. (1st February 2020) - Mandal, Uttam; Mandal, Santanu; Chakraborty, Bikash; Rizzoli, Corrado; Bandyopadhyay, Debasis
Graphical abstract: Highlights: Four new Schiff base complexes have been synthesized. A less-known amine has been used for the syntheses. Structures have been determined by single crystal X-ray diffraction studies. Abstract: Four new Schiff base complexes of first row transition metals viz. mononuclear [CoL3 ] (1 ), [NiL2 ] (2 ), [CuL2 ] (3 ) and binuclear [Cu2 L2 (NCS)2 ] (4 ) where HL = 2-[((2-(thiophene-2-yl)ethyl)imino)methyl]phenol, a bidentate Schiff base derived from 2-thiopheneethylamine and salicylaldehyde have been prepared. Characterization has been made with different physicochemical studies including single crystal X-ray diffraction. Structural studies indicate that the mononuclear complex 1 has a distorted octahedral geometry while 2 and 3 are square planar. On the other hand, 4 is a phenoxo-bridged binuclear species in which each copper(II) ion adopts a distorted square pyramidal geometry. In the solid states, intermolecular C–H⋯π or π⋯π interactions are operative in 2 and 4 .